Catalytic linkage between caspase activity and proteostasis in Archaea. (8th January 2019) - Seth‐Pasricha, Mansha; Senn, Stefan; Sanman, Laura E.; Bogyo, Matthew; Nanda, Vikas; Bidle, Kelly A.; Bidle, Kay D.
Summary: The model haloarchaeon, Haloferax volcanii possess an extremely high, and highly specific, basal caspase activity in exponentially growing cells that closely resembles caspase‐4. This activity is specifically inhibited by the pan‐caspase inhibitor, z‐VAD‐FMK, and has no cross‐reactivity with other known protease families. Although it is one of the dominant cellular proteolytic activities in exponentially growing H. volcanii cells, the interactive cellular roles remain unknown and the protein(s) responsible for this activity remain elusive. Here, biochemical purification and in situ trapping with caspase targeted covalent inhibitors combined with genome‐enabled proteomics, structural analysis, targeted gene knockouts and treatment with canavanine demonstrated a catalytic linkage between caspase activity and thermosomes, proteasomes and cdc48b, a cell division protein and proteasomal degradation facilitating ATPase, as part of an 'interactase' of stress‐related protein complexes with an established link to the unfolded protein response (UPR). Our findings provide novel cellular and biochemical context for the observed caspase activity in Archaea and add new insight to understanding the role of this activity, implicating their possible role in the establishment of protein stress and ER associated degradation pathways in Eukarya .